Kajian Hukum Pemeriksaan Selaput Dara dari Perspektif Ham dan Ditinjau dari Sistem Hukum Negara - Purwanto Panji Sasongko; Wiend Sakti Myharto, Sofiana; Sofiana; Muhammad Rafi Razan Darmawan (Jurnal Syntax Admiration, 2023)
Hymen examination is synonymous with the 'virginity test' which is a controversial examination by medical professionals. One of the famous myths about virginity is that 'virginity' is proven by writing the appearance of "intact hymen". Along with the times, this can also have an impact on the field of law, especially health law, that examination of the hymen which is carried out by medical professionals raises pros and cons. when viewed also from the side of Human Rights (HAM) and how it relates when faced with the State Law system for the sake of law. The form of this research is normative juridical research. with a conceptual approach (Conceptual Approach), while the type of research is descriptive exploratory using the philosophy of Integrative Law Theory. Examination of the hymen which can be called a virginity test is not allowed because it is not in accordance with the dignity of women and contains elements of discrimination. Medical examinations that aim to assist law enforcement include making a post mortem et repertum for someone sent by the police (investigators). The application of Article 133 of the Criminal Procedure Code in Indonesia is an application of the Continental European legal system. judicial medical experts (forensic doctors) can be included in the examination at the crime scene (TKP) in order to establish the cause of death and the manner of death.